2014
DOI: 10.1016/j.vaccine.2014.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Identifying human papillomavirus vaccination practices among primary care providers of minority, low-income and immigrant patient populations

Abstract: Objective Minority populations in the United States are disproportionally affected by Human Papillomavirus (HPV) infection and HPV-related cancer. We sought to understand physician practices, knowledge and beliefs that affect utilization of the HPV vaccine in primary care settings serving large minority populations in areas with increased rates of HPV-related cancer. Study Design Cross-sectional survey of randomly selected primary care providers, including pediatricians, family practice physicians and intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…31 Another study from the USA reported about 33% of physicians offering the HPV vaccine routinely to their eligible patients. 32 Investigations of the awareness and attitudes about the HPV vaccines among pediatricians, obstetricians and gynecologists in Turkey, showed that HPV vaccines were recommended by 59.4%, 82.6%, 66.7% and 80.6% of pediatricians, OBG specialists, OBG residents and pediatric residents, respectively. 33 High acceptability of the HPV vaccine was found among French general practitioners and the acceptability rate increased from 79.9% to 87.1% between the years 2007 and 2010.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another study from the USA reported about 33% of physicians offering the HPV vaccine routinely to their eligible patients. 32 Investigations of the awareness and attitudes about the HPV vaccines among pediatricians, obstetricians and gynecologists in Turkey, showed that HPV vaccines were recommended by 59.4%, 82.6%, 66.7% and 80.6% of pediatricians, OBG specialists, OBG residents and pediatric residents, respectively. 33 High acceptability of the HPV vaccine was found among French general practitioners and the acceptability rate increased from 79.9% to 87.1% between the years 2007 and 2010.…”
Section: Discussionmentioning
confidence: 99%
“…30,45,47 Studies assessing the relationship between provider characteristics and HPV vaccine recommendations most often focused on clinical specialty and demographics. Most studies found that pediatricians reported more positive HPV vaccine recommendation practices than family physicians 9,11,12,30,33,[48][49][50][51] or other types of providers. 12,32 Other studies failed to find variation in recommendations by specialty, 23,[34][35][36]40,52,53 but several of these studies did not include pediatricians.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
“…12,32 Other studies failed to find variation in recommendations by specialty, 23,[34][35][36]40,52,53 but several of these studies did not include pediatricians. 34,52,53 Most studies did not find variation in HPV vaccine recommendations by provider sex, 9,23,30,36,39,44,[47][48][49]54 but those that did most often favored female providers. 24,25,29,33,53 Similarly, most studies did not find variation in HPV vaccine recommendations by provider age or years in practice, 30,33,36,47,49 although a few did with mixed results.…”
Section: Preferences In Communication Source By Provider Typementioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In Italy, the vaccination is currently recommended and provided free for girls aged 11 and 12 y, and only in few geographic areas also for men. Numerous studies in different countries have evaluated individuals' knowledge, attitudes, and behaviors toward the vaccination mainly among health care providers, [9][10][11] adolescents, [13][14][15][16] and women and men for themselves [17][18][19][20][21][22][23][24][25] or for their adolescent daughters [26][27][28] or sons. [29][30][31] Unfortunately all these issues among young males have only been studied to a limited extent.…”
Section: Introductionmentioning
confidence: 99%